Serotypes and antimicrobial resistance of Streptococcus pneumoniae in Chinese pediatric population: a scoping review - Xu Han; Haiyang Yu; Niurka Molina Águila; María Eugenia Toledo Romaní (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
This review aimed to explore the serotype distribution and antimicrobial resistance of Streptococcus pneumoniae in the Chinese pediatric population based on literature published in the last six years. A scoping review was performed using PubMed and two Chinese databases: CNKI and WanFang Data. Of the total of 196 articles extracted, 14 studies were selected for this review. There are 13 articles that analyze the distribution of Streptococcus pneumoniae serotypes, the most frequently registered serotypes are: 19F, 19A, 23F, 14 and 6B. There are 11 articles that analyze the antimicrobial resistance of Streptococcus pneumoniae, the prevalence of non-susceptible to penicillin is in the range of 0% to 95.7%. Isolates are highly resistant to erythromycin, clindamycin, tetracycline, and trimethoprim-sulfamethoxazole; they are resistant to penicillin in pneumococcal meningitis but are sensitive to penicillin in other pneumococcal diseases, in addition, they are very sensitive to levofloxacin, vancomycin and Linezolid. It is concluded that the pneumococcal conjugate vaccine 13 has high coverage in Streptococcus pneumoniae serotypes in children from mainland China, therefore its inclusion in the childhood vaccination program is recommended; at the same time, the occurrence of serotype substitution should be taken into account. Therefore, more pediatric patients or children should be included in research, especially those under five years of age. Long-term, high-quality surveillance of the serotype distribution and antimicrobial resistance of Streptococcus pneumoniae is necessary for the development of pneumococcal disease prevention.